Emergence of antiphage functions from random sequence libraries reveals mechanisms of gene birth - Idan Frumkin; Christopher N. Vassallo; Yi Hua Chen; Michael T. Laub (Proceedings of the National Academy of Sciences, 2025)
De novo gene birth—the emergence of genes from nongenic sequences—drives biological innovation, yet its adaptive potential remains poorly understood. To investigate this issue, we screened libraries of ~100 million short (semi-)random sequences, mimicking early stages of gene birth, for genes that promote Escherichia coli survival during phage infection. This selection uncovered thousands of functional genes that confer viral resistance through at least two distinct mechanisms: 1) activation of a bacterial regulatory system that remodels the outer membrane, which provides broad-spectrum defense, and 2) transcriptional repression of bacterial outer membrane receptors required for phage adsorption, which provides phage-specific protection. Remarkably, unrelated random genes with no sequence similarity produced similar protective phenotypes, revealing that diverse sequences can converge on equivalent functions. We further showed that T4 phage rapidly evolves to counter these novel defenses, acquiring baseplate mutations that enhance adsorption to resistant hosts. Together, these findings demonstrate that random sequences can rapidly evolve into functional genes with direct fitness benefit, highlighting the evolutionary potential of de novo gene birth in the microbial world.